The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1998
DOI: 10.1128/mcb.18.2.960
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Damage Tolerance Pathways in Saccharomyces cerevisiae: a Requirement for Rev3 DNA Polymerase in Translesion Synthesis

Abstract: The replication of double-stranded plasmids containing a single N-2-acetylaminofluorene (AAF) adduct located in a short, heteroduplex sequence was analyzed in Saccharomyces cerevisiae. The strains used were proficient or deficient for the activity of DNA polymerase (REV3 and rev3⌬, respectively) in a mismatch and nucleotide excision repair-defective background (msh2⌬ rad10⌬). The plasmid design enabled the determination of the frequency with which translesion synthesis (TLS) and mechanisms avoiding the adduct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 46 publications
3
62
1
Order By: Relevance
“…Although psoralen monoadducts are substrates for NER, a single lesion on an extrachromosomally replicating plasmid did not greatly reduce the measured transformation level, perhaps because of replication of the undamaged strand (36). As with repair-proficient cells, monoadducts did not induce plasmid integration or conversion to His ϩ .…”
Section: Resultsmentioning
confidence: 90%
“…Although psoralen monoadducts are substrates for NER, a single lesion on an extrachromosomally replicating plasmid did not greatly reduce the measured transformation level, perhaps because of replication of the undamaged strand (36). As with repair-proficient cells, monoadducts did not induce plasmid integration or conversion to His ϩ .…”
Section: Resultsmentioning
confidence: 90%
“…In addition, we have carried out studies of TLS through a number of other DNA lesions-a cis-syn TT dimer, a (6-4) TT photoproduct, and an AAF adduct-that are also carried on a duplex plasmid. Also in this plasmid, replication initiates from a single-origin site and proceeds through a site-specific DNA lesion (Baynton et al 1998;Bresson and Fuchs 2002). From all these studies we conclude a requirement of Rad5 for TLS dependent upon Polz.…”
mentioning
confidence: 73%
“…It was suggested that MMR reduces the efficiency of recombination-mediated bypass when damage is present, and the studies presented here provide a concrete model for how the MMR system modulates pathway choice. Finally, our results may provide an explanation for the very low frequency (1-5%) of Pol -dependent lesion bypass observed in some plasmid-based yeast transformation studies (32,33), which contrasts with the high frequency (Ϸ60%) obtained when using lesion-containing singlestranded oligonucleotides (34,35). Based on the clear MMR dependence of TLS observed in the lys2⌬A746-NR system, we suggest that the specific use of MMR-defective host strains in the plasmid-based studies could account for the low TLS frequency.…”
Section: Discussionmentioning
confidence: 96%